Formation and Reactivity of Non-Stabilized Monomeric Alumoxane Intermediates - Grams, Samuel; Maurer, Johannes; Patel, Neha; Langer, Jens; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2022)
Several methods for the oxidation of the β-diketiminate AlI complexes (BDI)Al and (BDI*)Al with O2, Et3P=O or N2O are presented (BDI=HC[C(Me)N(DIPP)]2, DIPP=2,6-diisopropylphenyl; BDI*=HC[C(tBu)N(DIPP)]2). The selectivity of alumoxane formation depends strongly on the nature of the β-diketiminate ligand, the experimental procedure and the solvent. The mononuclear alumoxanes (BDI)Al=O and (BDI*)Al=O are highly reactive intermediates that cannot be isolated but either aggregate to give less reactive dimers or decompose by internal C−H activation of a backbone Me group or an iPr group. Ethereal solvents like Et2O react with alumoxanes to give (BDI)Al(OEt)OH and ethylene by β-H elimination. In case of N2O oxidation, subsequent reaction with a second equivalent of N2O to form the hyponitrite complexes (BDI)Al(N2O2) and (BDI*)Al(N2O2) is observed. Details of the alumoxane formation, reactivity and decomposition have been obtained by DFT calculations. These calculations also underscore their rather bipolar character, represented by the resonance structure (BDI)Al+−O−, and estimate the σ- and π-bond character of the Al=O bond at circa 76 % and 24 %, respectively.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Aluminium; Alumoxane; DFT calculations; Low-valent; β-diketiminate